2021
DOI: 10.3389/fbioe.2021.695053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tension on Human Periodontal Ligament Cells: Systematic Review and Network Analysis

Abstract: Orthodontic tooth movement is based on the remodeling of tooth-surrounding tissues in response to mechanical stimuli. During this process, human periodontal ligament cells (hPDLCs) play a central role in mechanosensing and mechanotransduction. Various in vitro models have been introduced to investigate the effect of tension on hPDLCs. They provide a valuable body of knowledge on how tension influences relevant genes, proteins, and metabolites. However, no systematic review summarizing these findings has been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 130 publications
5
41
1
Order By: Relevance
“…Interestingly, TNFRSF11B gene expression was below the detection limit in all experimental conditions in this study. In contrast, upregulation of TNFRSF11B has been reported previously in hPDLCs after exposure to static tensile strain for 12 h but not for longer periods of time [16,54,57]. Thus, one might assume that the TNFRSF11B gene is already upregulated by tensile strain in shorter time periods than covered in the present study.…”
Section: Effect Of Different Parameters Of Tensile Strain On Bone Remodelingcontrasting
confidence: 83%
See 4 more Smart Citations
“…Interestingly, TNFRSF11B gene expression was below the detection limit in all experimental conditions in this study. In contrast, upregulation of TNFRSF11B has been reported previously in hPDLCs after exposure to static tensile strain for 12 h but not for longer periods of time [16,54,57]. Thus, one might assume that the TNFRSF11B gene is already upregulated by tensile strain in shorter time periods than covered in the present study.…”
Section: Effect Of Different Parameters Of Tensile Strain On Bone Remodelingcontrasting
confidence: 83%
“…Similar results were obtained considering the specific anatomy of the PDL in vivo: application of 1 N and 3 N forces to incisors led to an increase in PDL width of ~12% [38]. A recent systematic review reported 10% tensile strain as the most frequently applied magnitude [16]. Herein, 10% tensile strain was selected as being equivalent to a physiological force exposure, whereas 20% cell stretching is commonly used to investigate the influence of pathogenic stimuli on cellular mechanotransduction in hPDLCs [39][40][41] and therefore was considered the upper limit of tensile strain in this study.…”
Section: Selection Of Tensile Strain Parameterssupporting
confidence: 74%
See 3 more Smart Citations